Pengaruh Pendidikan & Latihan dan Perilaku Individu terhadap Kinerja Pegawai Dinas Perhubungan Kota Solok - Irawan, Hendri (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2016)
This study aims to determine: (1) the influence of education and training and behavior of individuals on the performance of employees, (2) the effect of education and training on the performance of employees (3) the impact of individual behavior on employee performance the Department of Transportation Solok. This type of research is ex post facto. The study population was all employees of the Department of Transportation Solok. While the sample is total sampling of 41 people. Data taken with indirect communication technique using questionnaires as a data collection tool. The results of this study were (1) a significant difference and positive education and training and behavior of individuals on the performance of employees, (2) there is a significant effect and positive education and training on the performance of employees, (3) there is a significant and positive influence on the performance of individual behavior of employees at the Department of Transportation in Solok (a) education and training for employees often conducted by the Department of Transportation in Solok (b) the behavior of individual employees both categories (3.79) (c) performance employees were high (3.82) and means that employees often carry out activities that could improve its performance. Finally suggested to the leadership of the Department of Transportation Solok needs to be improved implementation of education and training for employees. Head of staff should be working to improve the motivation of work, work engagement and improve performance, especially indicators of quantity and quality of services to the community.